A Novel Strain of Orientia tsutsugamushi Detected from Chiggers (Acari: Trombiculidae) on Wild Rodents - Hak Seon Lee; Seong Yoon Kim; Hee Il Lee (Pathogens)
Scrub typhus is caused by intracellular bacteria belonging to the genus Orientia. Until 2010, the endemic region was thought to be restricted to the Asia–Pacific region. Orientia species have recently been discovered in South America, Africa, Europe, and North America. In accordance with these circumstances, we tried to find new or novel bacterial strains in the Republic of Korea (ROK). We found that a new strain of O. tsutsugamushi formed a unique clade based on a 56-kDa type-specific antigen gene and showed 63.2–77.8% similarity to other strains of the same species. Additionally, we identified another sequence with 99.8% similarity to the O3 strain, which has not been recorded in the ROK and whose pathogenicity remains unknown. These findings confirm the diversity of O. tsutsugamushi strains in the ROK, and highlight the need for continued surveillance and further studies to characterize the pathogenicity of this novel bacterial strain.